12 Reducing preoperative starvation time on the plastic surgery trauma list at a regional major trauma centre. (31st October 2017) - Fowler, Tim; Davies, Andrew; Dewi, Fion; Pang, Jonathan; Wright, Thomas
Abstract : Introduction and Aims: Pre-operative fasting is necessary to reduce the risk of regurgitation of gastric contents and pulmonary aspiration in patients undergoing general anaesthetic and procedural sedation. Excessive fasting is associated with metabolic, cardiovascular and gastrointestinal complications and patient discomfort. We aimed to reduce the fasting time for patients on the plastic surgery trauma list in a Major Trauma Centre. Methodology: Adult inpatients awaiting surgery were asked to complete a pre-operative assessment sheet. Questions included the length of pre-operative fasting, clarity of instructions and wellness scores. Patients who declined to participate or were unable to consent were excluded. The first cycle revealed the need for significant improvement. Interventions included staff education, patient information sheets, pre-operative drinks, greater availability of ward snacks and improved communication between the ward staff and surgical team through our electronic trauma database. Results: The initial audit of 15 patients revealed a mean fasting time of 16.3 hours for fluid (range 10–22) and a mean of 19.3 hours for solid food (range 10–24). The mean wellness score was 6/10 (10 being very well), 67% of patients felt they were given clear information. The final cycle demonstrated clear improvement in all domains. The mean fasting time declined to 5.1 hours (range 3–10 hours) for fluid and 13 hours (range 7.5–17 hours) for solid food. The mean wellness score (10=very well) increased from 6 to 8, the mean thirst score declined from 6.1 to 5.1% and 100% patients felt they had been given clear information. Conclusion: Removal of the traditional "NBM from midnight", patient education, a clear fasting routine with pre-operative drinks and improved communication between the full multidisciplinary team has led to a reduction in the fasting times on our trauma list.